Electromagnetic interference issues of power, electronics systems with wide band gap, semiconductor devices - Zare, Firuz; Kumar, D.; Lungeanu, M.; Andreas, A. (2015)
© 2015 IEEE. In this paper electromagnetic interference issues of power electronics systems with Wide Band Gap devices have been studied. The main advantages of these power switches are fast switching transient and high switching frequency capabilities which can improve efficiency of power electronics systems and reduce sizes of passive elements such as inductors and capacitors. Several conducted and radiated emission tests and efficiency measurement have been carried out to analyze the switching frequency and transient effects on harmonic emission and switching losses. The results have been compared with the same drive configuration, layout and enclosure but with conventional power switches (Si switches).